2010
DOI: 10.1136/jcp.2010.076752
|View full text |Cite
|
Sign up to set email alerts
|

Atypia in fine needle aspirates of breast lesions

Abstract: The presence of nuclear pleomorphism, high nucleus:cytoplasm ratio, epithelial cell atypia, low number of bipolar nuclei and necrosis are useful parameters to predict malignancy in atypical FNAC of the breast. Assessment of these factors in atypical FNAC may be helpful in predicting cancer risk and subsequent management decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
5
9
0
Order By: Relevance
“…The histological outcome of C3 FNACs was reported to be 30–45% malignant and 55–70% benign, with similar figures (30.1% malignant, 69.9% benign) demonstrated in the current and our previous study 8. Some authors recommend strict use of diagnostic criteria to avoid excessive reporting of C3 11 14 16 18…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The histological outcome of C3 FNACs was reported to be 30–45% malignant and 55–70% benign, with similar figures (30.1% malignant, 69.9% benign) demonstrated in the current and our previous study 8. Some authors recommend strict use of diagnostic criteria to avoid excessive reporting of C3 11 14 16 18…”
Section: Discussionsupporting
confidence: 88%
“…The investigation of cytological criteria associated with C3 cases revealed a number of features, confirming our previous findings 8. The cellularity of the specimen is fundamental in formulating a diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…In the practical setting, the C3 category is used when there is a level of diagnostic uncertainty. The number of C3 cases resulting in malignancy varies in the literature from 24.6 to 52% [19,20,21,22,23,24,25]. In this study, the overall rate of malignancy was 37.4%; however, the screening population yielded a much greater proportion of malignant outcomes at 50% when compared with the symptomatic population at 32%.…”
Section: Discussionmentioning
confidence: 61%
“…Confronting architectural patterns or cell morphological aberrations contribute to diagnostic uncertainties. These features reflect the heterogeneity of the C3 outcomes, which ranged from benign to malignant [22]. …”
Section: Discussionmentioning
confidence: 99%
“…We, like others have shown a heterogeneous mix of pathological outcomes during the follow up of C3 (5,(9)(10)(11)(12)(13)(14). In our earlier study, of 230 atypical (C3) cases, we found 37.4% to be malignant on follow-up and the remaining 62.6% yielded benign outcomes.…”
Section: Introductionsupporting
confidence: 50%